Pengaruh Gaya Kepemimpinan dan Remunerasi Terhadap Produktivitas Kerja Karyawan Kantor PT. XYZ - Andi Ray; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to determine the effect of leadership style and remuneration on work productivity of office employees of PT. XYZ. The variables used in this research are leadership style, remuneration, and work productivity. The data collection technique used was a questionnaire. This research is a quantitative study with a total sample size of 45 respondents who work in the PT. XYZ. The technique used in this research is purposive sampling which is part of the non-probability sampling. This study uses SPSS version 22 as a data processing tool. Data processing was analyzed by validity test, reliability test, classical assumption test, multiple linear regression analysis test, t test, f test, and determination coefficient test. Based on the results of the f test, F count > F table (91,544 > 2.11). This concludes that the variable leadership style and remuneration together have a significant effect on work productivity.